2018
DOI: 10.1016/j.gr.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the end-Ordovician glaciation on sediment routing systems: A case study from the Meseta (northern Morocco)

Abstract: Assessment of sediment redistribution by end-Ordovician ice sheets is crucial for the reconstruction of Lower Paleozoic source-to-sink patterns. Focussing on the ice-distal, deepwater Tazekka depocenter (Moroccan Meseta), we thus performed a provenance study that combined whole-rock geochemistry, petrography and insights from highresolution detrital zircon ages. The results show that the glacigenic sediments are compositionally-mineralogically and geochemically-more mature than preglacial strata. This observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 61 publications
1
30
0
1
Order By: Relevance
“…Nevertheless, the paleogeographic relevance of these structures is unclear, since they do not include suture‐related rocks (e.g., ophiolites), and the Ordovician‐Devonian stratigraphic successions in all the Moroccan Variscides, as well as in other zones of the northern margin of Gondwana, indicate deposition in a shared passive margin (Piqué, 1994; Simancas et al, 2009), suggesting that all the domains of the Moroccan Variscides remained attached to northern Gondwana throughout the Paleozoic. This paleogeographic affinity is also supported by the detrital zircon provenance studies performed to date (Abati et al, 2010; Accotto et al, 2019; Avigad et al, 2012; El Houicha et al, 2018; Ghienne et al, 2018; Letsch et al, 2018), which suggest a Gondwanan provenance for the Cambrian to Devonian sediments of the Moroccan Variscides. The only exception would be the Sehoul Block in the Western Moroccan Meseta (Figure 1b), which is thought to have an Avalonian derivation based on the presence of a mid‐Paleozoic (i.e., Caledonian) deformation that occurred before the emplacement of granites radiometrically dated at the Late Devonian (U‐Pb on zircons; Tahiri et al, 2010).…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…Nevertheless, the paleogeographic relevance of these structures is unclear, since they do not include suture‐related rocks (e.g., ophiolites), and the Ordovician‐Devonian stratigraphic successions in all the Moroccan Variscides, as well as in other zones of the northern margin of Gondwana, indicate deposition in a shared passive margin (Piqué, 1994; Simancas et al, 2009), suggesting that all the domains of the Moroccan Variscides remained attached to northern Gondwana throughout the Paleozoic. This paleogeographic affinity is also supported by the detrital zircon provenance studies performed to date (Abati et al, 2010; Accotto et al, 2019; Avigad et al, 2012; El Houicha et al, 2018; Ghienne et al, 2018; Letsch et al, 2018), which suggest a Gondwanan provenance for the Cambrian to Devonian sediments of the Moroccan Variscides. The only exception would be the Sehoul Block in the Western Moroccan Meseta (Figure 1b), which is thought to have an Avalonian derivation based on the presence of a mid‐Paleozoic (i.e., Caledonian) deformation that occurred before the emplacement of granites radiometrically dated at the Late Devonian (U‐Pb on zircons; Tahiri et al, 2010).…”
Section: Introductionmentioning
confidence: 63%
“…These populations are respectively related to primary sources of Cadomian/Pan‐African, Eburnean, and Liberian ages, which were formed by successive orogenies in northern Gondwana, and they are globally interpreted as indicative of West African Craton (WAC) affinity (e.g., Nance et al, 2008 and references therein). Recent U‐Pb geochronological data on detrital zircons from the Ordovician‐Devonian passive margin sequence of the para‐autochthonous Eastern Moroccan Meseta (Accotto et al, 2019; Ghienne et al, 2018) highlighted the presence of these detrital zircon populations and inferred their primary WAC affinity. In addition, these studies also found a Tonian–Stenian (c. 1 Ga) population and a Mesoproterozoic (c. 1.7–1.1 Ga) gap, which, considered together, point to NE‐Africa secondary sources (Saharan Metacraton and/orArabian‐Nubian Shield), instead of Grenville (Amazonian) sources (Accotto et al, 2019; Ghienne et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Moroccan Variscides north of the WAC, most of the previous detrital zircon studies focused on Cambro-Ordovician and Precambrian sedimentary sequences from the Anti-Atlas (Abati et al, 2010;Avigad et al, 2012), Middle Atlas, Western Meseta and Coastal Block Ghienne et al, 2018;Letsch et al, 2018), all of them having highlighted a strong WAC affinity. Very similar results were obtained on Triassic sandstones and siltstones of the High Atlas (Domènech et al, 2018;Marzoli et al, 2017) and Middle Atlas (Pratt et al, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Braid et al, 2011;Fernández-Suárez et al, 2014;Linnemann et al, 2004Linnemann et al, , 2008Pereira et al, 2017;Pérez-Cáceres et al, 2017;Shaw et al, 2014), but only a few works have focused on the Moroccan Meseta Variscides (ensemble of the Variscan domains cropping out in Morocco;e.g. El Houicha et al, 2018;Ghienne et al, 2018;Letsch et al, 2018;Pérez-Cáceres et al, 2017).…”
Section: Introductionmentioning
confidence: 99%